2009
DOI: 10.1002/rcm.3976
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of 13C‐ and 15N‐isotopic enrichments of threonine by mass spectrometry

Abstract: Under conditions of high isotopic dilution, e.g. in a tracer study, the ability to determine accurately and quantitatively small variations in isotopic enrichments of differently labelled chemical compounds (e.g. (13)C and (15)N in threonine) in a single run by gas chromatography/mass spectrometry (GC/MS) is desirable but remains a technological challenge. Here, we report a new, rapid and simple GC/MS method for simultaneously measuring the isotopic enrichments of doubly labelled threonine ([U(13)C] and (15)N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…To study intestinal mucin synthesis, isotopically labeled threonine was administered because muc 2 is rich in threonine. Outcomes have been observed in rats (Faure et al, 2005(Faure et al, , 2007, pigs (Puiman et al, 2011), and neonates (Schaart et al, 2009;Godin et al, 2009). Nutritional interventions (e.g., the effects of pro-or prebiotics) could be studied using this method, but no clinical studies have yet been performed.…”
Section: F Mucin Synthesismentioning
confidence: 98%
“…To study intestinal mucin synthesis, isotopically labeled threonine was administered because muc 2 is rich in threonine. Outcomes have been observed in rats (Faure et al, 2005(Faure et al, , 2007, pigs (Puiman et al, 2011), and neonates (Schaart et al, 2009;Godin et al, 2009). Nutritional interventions (e.g., the effects of pro-or prebiotics) could be studied using this method, but no clinical studies have yet been performed.…”
Section: F Mucin Synthesismentioning
confidence: 98%
“…In a first attempt, simultaneous measurements of 13 C-and 15 N-isotopic enrichments of threonine were carried out by GC/MS using an intense electron ionization (EI) fragment and applying mathematical corrections [21]. Popa et al used co-feeding of 13 C and 15 N (H 13 CO 3 -and 15 N 2 ) to study the relationship between CO 2 and N 2 fixation in filamentous nitrogen-fixing cyanobacteria [22].…”
Section: Introductionmentioning
confidence: 99%
“…A number of protocols exploiting isotope ratio measurement by mass spectrometry (irm-MS) interfaced via a combustion furnace to gas chromatography (GC-irm-MS) for the determination of the d 13 C and d 15 N values of a-amino acids at or near natural abundance have been reported. [1][2][3][4] While this analytical approach has the advantage of not requiring the use of highly isotopically-enriched starting materials, it has the disadvantage of requiring the derivatization of amino acids to provide sufficient volatility to permit a GC separation prior to stable isotope determination. In order to measure the d 13 C and d 15 N values by GC-irm-MS, it is necessary that the derivatization reagents: (i) react quantitatively with all target analytes; (ii) lead to minimal isotopic dilution (i.e.…”
mentioning
confidence: 99%
“…Methods have been reported that avoid the use of TMS derivatives. Andresen et al 17 used a large-scale multi-step reaction to convert taurine into N-carbobenzyloxytaurine amide for the MS analysis of 2% enriched [1,[2][3][4][5][6][7][8][9][10][11][12][13] C]taurine, while Irving and Klein 18 reported a method for the GC-MS analysis of the N,N-dimethylaminomethylene methyl ester of taurine. However, these derivatization reactions are not suitable for determining the d 15 N of taurine, since they involve the addition of one exogenous nitrogen atom, which would reduce the precision of measurement.…”
mentioning
confidence: 99%
See 1 more Smart Citation